The Effect of Anise and Rosemary on Broiler Performance - Al-Kassie, Ghalib Alwan Mohammed (International Journal of Poultry Science, 2008)
The present study was conducted to explore the usage of different level of Anise and Rosemary in broiler nutrition as a natural growth promotion. Different levels were added to a standard diet, to determine its effect on the daily feed intake, daily live weight and feed conversion ratio compared to a control group. Two hundred fifty day-old broilers(Arbor Acre)were divided into five equal groups as follows, Control group (no addition of Anise and Rosemary), Anise 0.5%, Anise 1%, Rosemary 0.5% and rosemary 1%. The experiment carried out in 42 days. The feed intake was significantly (P<0.05) different between the groups. The highest was at Anise 1% group and the highest daily live weight gain observed in the same group Anise 1% (63.34g) followed by Anise 0.5% group (59.49g), Rosemary 1% group (59.30g), Rosemary 0.5% group (56.08g) and control group (50.99g). The results show that Anise 1% and Rosemary 1% could be considered as a potential growth promoter for poultry.